2023
DOI: 10.28991/cej-2023-09-09-012
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aspect Ratio, Characteristic Strength and Compression Rebars on the Shear Capacity of Shallow RC Beams

Ahmed A. Soliman,
Dina M. Mansour,
Ayman H. Khalil
et al.

Abstract: This paper investigates the impact of the aspect ratio, the characteristics strength of the concrete, and the compression steel ratio on the shear capacity of wide-shallow beams. An experimental program consists of seven specimens, including a control specimen, all tested under a three-point load test. Three specimens were considered for each parameter (the control specimen was included in all three variables). The experimental results were compared to the theoretical values of six different codes of practice;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Since all the tested beams have the same dimensions, concrete strength, and longitudinal rebars, they all have the same concrete contribution and longitudinal rebar contribution (vc+v), and only the shear reinforcement contribution (vs) is responsible for the difference in total shear strengths. Plotting the total shear strength (vu) of beams B1, B6, and B7 against their theoretical ultimate shear reinforcement strength (4 stirrups × Ash.fys) as shown in Figure 5-c showed that (vc+v) equals 1.24 MPa for all the samples, which matches the results of the first part of this research [3]. The difference between (vu) and (1.24 MPa) is (vs).…”
Section: Shear Capacitysupporting
confidence: 80%
See 1 more Smart Citation
“…Since all the tested beams have the same dimensions, concrete strength, and longitudinal rebars, they all have the same concrete contribution and longitudinal rebar contribution (vc+v), and only the shear reinforcement contribution (vs) is responsible for the difference in total shear strengths. Plotting the total shear strength (vu) of beams B1, B6, and B7 against their theoretical ultimate shear reinforcement strength (4 stirrups × Ash.fys) as shown in Figure 5-c showed that (vc+v) equals 1.24 MPa for all the samples, which matches the results of the first part of this research [3]. The difference between (vu) and (1.24 MPa) is (vs).…”
Section: Shear Capacitysupporting
confidence: 80%
“…Soliman et al [3] had investigated the shear capacity of seven wide-shallow beam specimens, considering the aspect ratio, concrete compressive strength, and ratio of compression rebar. The ultimate shear strength of the specimens decreased when the aspect ratio increased from 1.66 to 5.…”
Section: Introductionmentioning
confidence: 99%